Promotion of bone repair of rabbit tibia defects induced by scaffolds of P(VDF-TrFE)/BaTiO 3 composites - Gimenes, R.; Zaghete, M. A. [UNESP]; Espanhol, M.; Sachs, D.; Silva, M. R.A. (Springer Nature, 2019)
In this work, scaffolds made of a novel experimental 0–3 type composite were implanted onto non-critical defects in rabbit tibiae. This work discusses the bone repair promoted by polyvinylidene fluoride-trifluoroethylene P(VDF-TrFE)/barium titanate(BaTiO3) composite that scaffolds with 10 vol% BaTiO 3. Prior to implant surgery, the P(VDF-TrFE)/BaTiO 3 scaffolds, moulded into a membrane disk, were subjected to a cytotoxicity test (ASTM F895-84). A standardized transverse osteotomy was made with the following dimensions: 4.5 mm in width by 9 mm in length, at the proximal tibial metaphysis, in adult male rabbits, by using a cylindrical drill, cooled with a physiologic solution. These critical defects were filled with blood clot on the left tibiae (control group), whereas the right tibiae were covered with composite scaffolds, measuring 5 mm in thickness and 10 mm in diameter (experimental group); n= 12 for each group. After 21 days, the rabbits were sacrificed and the tibiae bone fragments were conducted to demineralization routines, from fixation and stain procedures to histological analysis. The scaffolds promote the growth of the bone, resulting in an increased repair with callus formation around the scaffold and high mitotic activity at newly formed bones.
Keywords: bone repair; P(VDF-TrFE)/BaTiO 3 composites; Scaffolds